Undergraduate Nursing Students’ Experiences of Virtual Learning during the COVID-19 Pandemic: A Qualitative Study - Zahra Asgari Tapeh; Azar Darvishpour (Nursing Research and Practice)
Background. With the emergence of the COVID-19 pandemic, schools and universities were closed, and virtual education replaced face-to-face classes. This learning method was a new and different experience for nursing students. Perceiving their experiences could help improve the quality of medical education. Therefore, the present study aimed to describe nursing students’ experiences of virtual learning during the COVID-19 pandemic. Materials and Methods. This study involved qualitative descriptive research that was conducted in 2022. The participants included 25 undergraduate nursing students studying at the School of Nursing and Midwifery in East Guilan in northern Iran who had experienced virtual learning due to the COVID-19 pandemic. Purposeful sampling was applied until data saturation. Qualitative content analysis with a conventional approach was performed based on the model proposed by Graneheim and Lundman (2004). Coding was performed with MAXQDA 2007 software. Results. The data analysis led to the emergence of 110 primary codes and two main categories entitled “positive experiences” and “negative experiences.” The first main category was “positive experiences” (included 1 subcategory (benefits of virtual learning) with 3 subsubcategories (saving time, saving money, and increasing the possibility of daily planning)). The second main category was “negative experiences” (included 4 subcategories (reducing quality of education, physical effects, psychological effects, and different exams)). Conclusion. Nursing students had both positive and negative experiences with virtual learning during the COVID-19 pandemic and were facing multiple educational challenges. The findings of this study could be considered by managers and relevant officials in educational planning to improve the quality of nursing education.